Search
Ask a question
1

solve 5(2z-3) = 9(z-3)

I need this problem solved.
 

1 Answer by Expert Tutors

Tutors, sign in to answer this question.
Megan H. | Math Tutoring - All GradesMath Tutoring - All Grades
5.0 5.0 (307 lesson ratings) (307)
1
Check Marked as Best Answer
Think Order of Operations, PEMDAS, parentheses, exponents, multiply and divide, add and subtract.
 
First you have to distribute the 5 on the left side and the 9 on the left side to each term in the corresponding parentheses. 
5(2z-3)=9(z-3)
5*2z-5*3 = 9*z-9*3
10z-15 = 9z-27
then add 15 to both sides
10z=9z-12
then subtract 9z from both sides
z=-12
that's your answer!  Just go through the order of operations and remember whatever you do to one side of the equation you must do to the other.